Corrosion of ceramic materials - McCauley, Ronald A., 1942- (Corrosion technology, 2013)
"This popular book helps readers address corrosion problems and create the most corrosion-resistant systems possible. It examines corrosion by gases, liquids, and solids and presents various models for evaluating corrosion. Now suitable as a graduate-level text, this expanded and completely reorganized third edition incorporates several new chapters along with recent literature and research findings. New chapters cover biological sources of corrosion, bioceramics, building materials, and restoration techniques. This edition also adds more end-of-chapter questions and additional reading lists"--